Sosialisasi Pemanfaatan Puding Daun Kelor sebagai Makanan Pendamping Asi dan Gizi untuk Mencegah Stunting - Niswar, Dedi; Kasmawati, Kasmawati; B, Ahmad Nurul Ihsan (Universitas Nusantara PGRI Kediri, 2025)
The socialization of the use of Moringa leaf pudding as a complementary food for breast milk and nutrition to prevent stunting aims to evaluate the effectiveness of the socialization of the use of Moringa leaf pudding as an effort to increase nutritional consumption in target groups, for example, pregnant women and toddlers. This socialization was carried out through a knowledge transfer analysis method regarding the benefits of Moringa leaves and how to make pudding to increase people's creativity and be able to utilize one of the natural products as a healthy food product, apart from that it can influence the increase in vegetable consumption among the community. These findings identify that the use of Moringa leaf pudding is an effective strategy in increasing nutritional intake and food diversification. Therefore, the transmission of knowledge and practice in this socialization is an initiative and can be accepted by the community and has the potential to be further developed as a simple functional food product that is nutritious and easily affordable in the surrounding environment. Apart from improving the quality of people's creativity and healthy lifestyles in the daily environment, there are also the results of socialization that has been implemented specifically to prevent stunting, pregnant women and toddlers can increase cooperation and support the welfare of society in general. And also the results of this activity show an increase in community knowledge and can trigger the formation of micro, small and medium enterprises (MSMEs), based on local resources.